Off-label short-term use of thiocolchicoside (Tiyozid®) in the clinical therapy of fibromyalgia - Valentina Reshkova; Simeon Monov; Alexander Mandadjiev (Pharmacia)
Summary: Fibromyalgia (FM) is a complex, chronic, nondegenerative musculoskeletal disorder of unknown etiology, and it requires a different clinical approach for every patient. Objectives: The present clinical follow-up observes the effect of the central-acting myorelaxant thiocolchicoside (Tiyozid®) on clinical manifestations in patients with primary fibromyalgia. Methods: The following article presents a prospective clinical follow-up in eighteen ambulatory women with primary fibromyalgia observed in 41 days. Results: A significant difference between the 1st and 41st day of treatment with thiocolchicoside (Tiyozid®) 4 mg tablets in the mean number of pain points (15.4 ± 1.9 vs. 13.17 ± 1.5, p < 0.05), an increase in pain threshold (2.37 ± 0.4 to 2.58 ± 0.3, p > 0.05), and a decrease in the degree of chronic fatigue (7.1 ± 0.8 vs. 3.5 ± 1.3, p < 0.05). On the 41st day, the overall impact of treatment with thiocolchicoside on quality of life showed a significant improvement (37.5 ± 11 vs. 28 ± 8, p < 0.05). Conclusion: As a short-term therapy, thiocolchicoside (Tiyozid®) has a positive effect on clinical manifestations in patients with primary fibromyalgia, which affects everyday activities and improves their quality of life.